New‐onset non‐lesional aphasic status epilepticus. Clinical description, diagnostic clues, and treatment algorithm. (7th February 2022) - Jaraba Armas, Sonia; Sala‐Padró, Jacint; Veciana, Misericòrdia; Arroyo, Pablo; Pedro, Jordi; Mora, Jaume; Fernandez, Montserrat; Camins, Àngels; Rodriguez‐Bel, Laura; Falip, Mercè
Abstract: Objectives: De novo aphasic status epilepticus (ASE) in patients without a previous history of epilepsy and without cerebral lesions (aphasic NOSE) is rare. The aim of the study is to describe its clinical characteristics, etiologies, and outcome. Materials & Methods: Single‐center study including consecutive patients presenting to the emergency department between 2011 and 2019 with acute aphasia, which was finally diagnosed as aphasic NOSE. Subsequent episodes of aphasia (>5 min) were recorded and divided into confirmed ASE and postictal aphasic episodes (non‐ASE). Clinical characteristics of the two types of episodes were compared. Results: Nineteen patients were included, suffering fifty episodes of epileptic aphasia, episodes per patient 2.6 (range 1–7). Fifteen patients (71.4%) were women, mean age at ASE onset was 66.05 years old (SD 6.3). Nine (47%) patients died, 6 of them (66.7%) during the aphasic episode. Ictal EEG was available in 37 episodes, confirming the diagnosis of ASE in 12 episodes; in 8 episodes, the EEG fulfilled the criteria of possible ASE. The most frequent etiologies were inflammatory and vascular. Comparing ASE with non‐ASE episodes, ASE was longer than non‐ASE (225 vs 65 h, p .024) and was treated more frequently with BZD (76 vs 24%, p .001) but with a longer delay (22.2 vs 1.5 h, p .06). Conclusions: ASE is a treatable, highly relapsing emergency, with the subsequent relapses ASE or postictal aphasia. EEG is diagnostic in half of the patients, while in others imaging techniques are also useful. Benzodiazepines should be administered. Persistent aphasia, of more than 65 hours' duration, is highly suggestive of ASE.